Bio-Energy Connectivity And Ecosystem Services. An Assessment by Pandora 3.0 Model for Land Use Decision Making - Pelorosso, Raffaele; Gobattoni, Federica; Geri, Francesco; Monaco, Roberto; Leone, Antonio (TeMA - Journal of Land Use, Mobility and Environment, 2014)
Landscape connectivity is one of the major issues related to biodiversity conservation and to the delivery of Ecosystem Services (ES). Several models were developed to assess landscape connectivity but lack of data and mismatching scale of analysis often represent insurmountable constraints for the correct evaluation and integration of ecological connectivity into plans and assessment procedures. In this paper a procedure for ES assessment related with Habitat and Bio-Energy Landscape Connectivity (BELC) is proposed. The method is based on the connectivity measure furnished by the last version of PANDORA model and uses a modified formulation of current ES evaluation. The implementation of the model in a real case has highlighted its potential multi-scale workability. The spatial approach of the model aims at furnishing a further tool for the spread of ES and landscape ecology concepts into procedures of assessment (e.g. EIA, SEA) and land use planning at different administrative scales.